State Tax Differentials, Cross-Border Commuting, and Commuting Times in Multi-State Metropolitan Areas - David Agrawal; William H. Hoyt (Center for Economic Studies and ifo Institute (CESifo), 2014)
We examine the effects of differences in income tax rates on commuting times within multi-state MSAs. Our theoretical model introduces a border into a model of an urban area and shows that differences in average tax rates distort commute times and interstate commutes. Empirically examining multi-state MSAs allows us to exploit tax policy discontinuities while holding fixed other characteristics. We identify large effects on commuting times for affluent households and homeowners in MSAs in which taxes are based on the state of residence. We discuss how the model and empirical design can be used to study other policy differences.
Keywords: H20; H71; H73; R12; R28; R41; 330; tax differentials; transportation; inter-jurisdictional competition; commuting